Effectiveness of anastomotic reinforcement sutures in reducing anastomotic leakage risk after laparoscopic rectal cancer surgery: a pooled and integration analysis - Yue, Yumin; Zhang, Xiaolong; Qu, Yaqi; Zhao, Xu; Ding, Fanghui; Li, Jiang; Zheng, Bobo (Frontiers in Oncology, 2024)
Background and objectives: Anastomotic leakage (AL) is one of the most serious complications after laparoscopic anus-preserving surgery for rectal cancer, which significantly prolongs the patient's hospital stay, leads to dysfunction, and even increases the patient's perioperative morbidity and mortality, and little is known about the effectiveness of anastomotic reinforcement sutures to prevent AL. Thus, this study was conducted to evaluate the efficacy of anastomotic reinforcement sutures as a means to prevent AL during laparoscopic surgery for rectal cancer. Methods: A comprehensive and systematic search was performed in the literature database by combining subject and free terms up to October 10, 2023. The overall literature included was integrated and analyzed using Stata 12.0 software and Review Manager version 5.4 software to assess the effect of anastomotic reinforcement sutures on the incidence of AL. Results: A total of 2452 patients from 14 studies were included, and an integrated analysis showed that the use of anastomotic reinforcement sutures significantly reduced the incidence of AL (OR=0.26, 95% CI:0.18-0.37, P<0.00001, I 2 =0%). However, the findings confirmed whether or not the anastomosis was reinforced with sutures did not affect the incidence of anastomotic stenosis (OR=0.69, 95% CI:0.37-1.32, P=0.27, I 2 =0%). We performed subgroup analyses of the results of the study, the randomized controlled studies (OR=0.31, 95%CI:0.15-0.65, P<0.001)as well as retrospective studies(OR=0.28, 95%CI:0.19-0.41, P<0.001),3-0 sutures (OR=0.28, 95%CI:0.17-0.45, P<0.001 )versus 4-0 sutures(OR=0.26, 95%CI:0.13-0.53, P<0.001), barbed wire sutures(OR=0.26,95%CI:0.14-0.48, P<0.001)versus non-barbed wire sutures(OR=0.30,95%CI:0.20-0.46, P<0.001), interrupted(OR=0.30,95%CI:0.20-0.46, P<0.001) versus continuous sutures (OR=0.29,95%CI:0.16-0.51, P<0.001) to the anastomosis, full-thickness suture (OR=0.29,95%CI:0.16-0.51, P<0.001)versus sutured with the seromuscular layer (OR=0.27,95%CI:0.14-0.53, P<0.001), anastomotic sutured in one (OR=0.27,95%CI:0.14-0.53, P<0.001)versus non-one circle (OR=0.30,95%CI:0.20-0.44, P<0.001), and reinforcing sutures to the dog-ear area(OR=0.26,95%CI:0.14-0.50, P<0.001) versus the non-non-dog-ear area (OR=0.30,95%CI:0.20-0.45, P<0.001), have suggested that there is no significant difference between each other and that all of them reduce the incidence of AL. This study provides evidence that performing reinforcement suturing of the anastomosis during laparoscopic rectal surgery significantly lowers the incidence of postoperative anastomotic leakage. but has no significant effect on anastomotic stenosis. It is important to note that further randomized controlled studies are required to confirm this conclusion.